The redesign of provincial road geometric used AutoCAD®2D: A case Jalan Majalengka-Rajagaluh, Indonesia - Anugraha, Pebri Tri; Rifai, Andri Irfan; Taufik, Mohamad; Isradi, Muhammad (International Journal Labs, 2024)
Jalan Majalengka-Rajagaluh is a road located in several sub-districts that is a link to the city and one of the connecting roads to Cirebon City. This design planning began in Cigasong sub-district and continued to Rajagaluh sub-district with a length of 5.3 kilometers on the Majalengka-Rajagaluh road. The results of the geometric design are visualized in the form of drawings using AutoCAD 2D. The design speed (Vd) is set at 60 km/h with a horizontal curve radius of 358 m, a maximum slope of 4%, and an elevation (e max) of 8%. Based on this design criterion, a spiral curve with a circular arch length (Lc) of 74,996 m was obtained. Furthermore, the results of the calculation of the vertical alignment of the length (L) of one type of convex curve in the PPV are also calculated.